Kemampuan Berpikir Kritis Mahasiswa pada Materi Pemantulan Cahaya melalui Model Pembelajaran Susan Loucks Horsley (SLH) - Roudhoutul Aulia Rochim; Wulandari, Desi; Af'idah, Noer; Hayati, Nur; Arinna Manasikana, Oktaffi (Pusat Riset dan Inovasi Nasional, 2025)
Critical thinking skills refer to the ability to analyze assumptions, distinguish hidden values, evaluate evidence, and assess conclusions. This study aims to develop students' critical thinking skills by implementing the Susan Loucks-Horsley (SLH) learning model. The type of research conducted is pre-experimental with a one-shot case study design. The research was carried out in the 2020 Science Education Study Program, Class A, at Hasyim Asy’ari University, with a total sample of 33 students. The subject matter in this study was light reflection. Data collection was conducted using essay tests based on critical thinking skill indicators. Based on data analysis, it can be concluded that the students' average critical thinking ability was 85%, categorized as very high, with 22 students in the very high category and 11 students in the high category. The average mastery of critical thinking indicators also fell into the very high category, with the following details: elementary clarification (96%), the basis for decisions (82%), inference (75%), advanced clarification (89%), and supposition and integration (83%).